Efeitos da exposição intraoral e da aplicação de tratamentos de limpeza sobre arcos ortodônticos de aço inoxidável - Mattiello, Fabiano Dalla Lana (2014)
Introduction: The purpose of this study was to to evaluate the effects of the intraoral aging on the stainless steel (SS) archwire surface and the effects of four methods of archwire cleaning on the variables of debris, roughness, and friction during sliding mechanics. Methods: Seventeen segments of as-received 0.019 × 0.025 inch SS archwire, without bends, was designated as C- group, while 85 segments of 0.019 × 0.025 inch SS archwire were removed from the intraoral environment after four weeks of exposure. These retrieved segments were divided into 5 groups of 17 segments each: C+ (clinical use control group), T1 (sodium bicarbonate jet cleaning), T2 (77oGL alcohol soaked gauze cleaning), T3(ultrasound cleaning) and T4 (steel wool sponge cleaning).The debris level of all those 6 groups were observed by scanning electron microscopy. The Ra was evaluated with a rugosimeter and frictional force was evaluated by the displacement of the segments through the bracket slots assembled in the universal testing machine. The plate containing the bracktes was attached in the machine upper grip to slide at a speed of 5 mm/minute for a distance of 5 mm. Data were analyzed by ANOVA, Student s t-test, Mann-Whitney and Student-Newman-Keuls tests, with α=0,05. Results: The debris of C+ (mean score 2) group increased significantly (p<0.001) in comparison to C- (mean score 0). After the cleaning procedures, only the T2 (p<0.05) and T4 (p<0.01) groups, both with mean score 1, showed significantly decrease in the debris scores. The Ra analysis showed that C+ (mean 0,41μm) group had an increase (p<0.001) in Ra level in comparison to C- (mean 0,18μm), while only the T4 group (mean 0,25μm) showed a decrease after cleaning method in comparison to C+ (p<0.05). The frictional force levels did not show significant difference between C- (mean 6,90N) and C+ (mean 7,89N) groups (p>0.05) and between C+ and T1 (mean 5,73N), T2 (mean 9,49N), T3 (mean 8,56N) and T4 (mean 9,09N) groups (p>0.05). Conclusions: The debris and Ra of SS rectangular wires increased significantly during clinical use, however without causing a significant increase in the frictional force level. The alcohol soaked gauze and the steel wool sponge cleaning methods promoted a significant decrease in the debris scores of retrieved archwires, while the roughness of these archwires decreased only with the steel wool sponge cleaning method. The resistance to sliding of retrieved archwires was not affected by any of the four cleaning methods.